Lewis acid-promoted synthesis of highly substituted pyrrole-fused benzoxazinones and quinoxalinones. Issue 3 (1st February 2021) - Selvendran, Suresh; Rajendran, Saravanakumar
Abstract: A synthesis of a series of novel fused tricyclic heterocyclic compounds has been achieved in one-pot reaction set up starting from ( E )-3-(2-oxo-2-phenylethylidene)indolin-2-one and 1, 4-benzoxazinone/quinoxalinone derivatives promoted by tin(IV) chloride. The reaction is supposed to occur via a sequential intermolecular Michael addition of the 1, 4-benzoxazinone derivatives to the oxindoles, intramolecular cyclization, and aromatization with the elimination of water. Apart from spectroscopic characterization, the structure of one of the pyrrolo[1, 4]benzoxazinone derivative is confirmed by single-crystal X-ray diffraction. Thus, the developed domino protocol provides easy access to multifunctional pyrrolo[1, 4]benzoxazines in one-pot with high efficiency. Graphical Abstract: